Hit the deck [videorecording (DVD)] - Rowland, Roy; Powell, Jane, 1929-2021-; Martin, Tony, 1913-2012; Reynolds, Debbie; Pidgeon, Walter, 1897-1984; Damone, Vic; Raymond, Gene; Miller, Ann, 1923-2004; Tamblyn, Russ; Naish, J. Carrol, 1896-1973; Darwell, Jane, 1880-1967; King, Alan, 1927-2004; et al. (Classic musicals from the dream factory, 2008)
Sailor Danny Xavier Smith and two other guys try to save his sister Susan's virtue. She wants to get a role in the show "Hit the Deck". After wrecking the producers hotel suite, they land in the brig. But Danny's father is a Rear Admiral ...